FINANCIAL SECTOR INTEGRATION AND CREDIT RISK IN DRIVING SECTORAL ECONOMIC PERFORMANCE: EVIDENCE FROM THE DUAL BANKING SYSTEM IN NORTH SUMATRA - Nuzulia, Nuzulia; Hotsawadi, Hotsawadi; Kasanah, Roisatun (Elastisitas : Jurnal Ekonomi Pembangunan, 2026)
This study examines the role of financial sector integration through conventional and Islamic banking in driving sectoral economic performance in North Sumatra Province. It analyzes the impact of credit expansion and financing risk, proxied by Non-Performing Loans (NPL) and Non-Performing Financing (NPF), on sectoral output within a dual banking system framework. This study employs panel data covering 21 economic sectors in North Sumatra and applies both static panel estimation methods (Fixed Effects Model and Random Effects Model) and dynamic panel approaches (System-GMM and First-Difference-GMM) to address heterogeneity and potential endogeneity issues. The results indicate that credit expansion has a positive and significant effect on sectoral output, suggesting that financial integration enhances regional productive capacity. In contrast, higher levels of NPL/NPF negatively affect sectoral performance, reflecting weakened intermediation due to deteriorating asset quality. Robustness tests confirm the consistency and validity of the estimation results across different model specifications. These findings highlight the importance of maintaining a balance between credit growth and prudent risk management to support sustainable regional economic development.